Doctoral research in Italian studies in Poland: over sixty years in the history of a discipline - Słapek, Daniel (Kwartalnik Neofilologiczny, 2026)
The article analyzes doctoral dissertations in Italian Studies defended in Poland from the beginnings of the discipline up to 2025 (177 theses). It reconstructs the main lines of research development, focusing on thematic evolution, the geographical distribution of academic centers, and the role of supervisors. Particular attention is devoted to the modes of publication of the dissertations, examined with regard to place of publication, time to publication, and type of publisher.